2016
DOI: 10.1515/hepo-2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant toxicities of essential oils and two monoterpenes against potato tuber moth (Phthorimaea operculellaZeller)

Abstract: SummaryIntroduction:The potato tuber moth (PTM) is the major economic pest of potato. Different approaches were tried to prevent and control this pest including natural pesticides and synthetic fumigants.Objectives: This study was conducted to evaluate the insecticidal activity of the essential oils of thyme and myrtle. In addition to evaluating the insecticidal activity of carvacrol and eucalyptol against the different life stages of potato tuber moth using a fumigation bioassays.Methods:Thyme and myrtle oils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…When germinating, the crop should be thoroughly earthed up for 30-40 days after planting [59]. To prevent further dispersion, it is necessary to focus on the management of the potato tuber moth, using, for instance, microbial control or fumigation [60][61][62][63]. In addition, Chandel and Chandla [8] reported that Bacillus thuringiensis and granulosis virus can reduce the infection rate of the potato tuber moth from 4.17%-8.59% to 0.32%-0.87%.…”
Section: Risk Analysis Of the Potato Tuber Moth Distribution Based Onmentioning
confidence: 99%
“…When germinating, the crop should be thoroughly earthed up for 30-40 days after planting [59]. To prevent further dispersion, it is necessary to focus on the management of the potato tuber moth, using, for instance, microbial control or fumigation [60][61][62][63]. In addition, Chandel and Chandla [8] reported that Bacillus thuringiensis and granulosis virus can reduce the infection rate of the potato tuber moth from 4.17%-8.59% to 0.32%-0.87%.…”
Section: Risk Analysis Of the Potato Tuber Moth Distribution Based Onmentioning
confidence: 99%
“…The applied oil concentrations were chosen to identify the one that achieve a 100% mortality. Fumigation experiments were designed as reported in a previous study [10]. Adults and larvae were fumigated in jars, (1 liter air volume), while eggs and pupae, (3-5 days old), were fumigated in Petri dishes,(160 cm 3 air volume).…”
Section: Fumigation Experimentsmentioning
confidence: 99%
“…The toxic effects of citronellol and nerol against adult insects (one day old) were investigated as reported in a previous study [10]. Adults were considered dead when no leg or antennal movements were observed.…”
Section: Fumigation Experimentsmentioning
confidence: 99%
See 2 more Smart Citations